Neuroendocrine mechanisms that connect feeding behavior and stress - Zane Andrews (Frontiers Research Topics, 2015)
Research during the past decade highlights the strong link between appetitive feeding behavior, reward and motivation. Interestingly, stress levels can affect feeding behavior by manipulating hypothalamic circuits and brain dopaminergic reward pathways. Indeed, animals and people will increase or decrease their feeding responses when stressed. In many cases acute stress leads to a decrease in food intake, yet chronic social stressors are associated to increases in caloric intake and adiposity. Interestingly, mood disorders and the treatments used to manage these disorders are also associated with changes in appetite and body weight. These data suggest a strong interaction between the systems that regulate feeding and metabolism and those that regulate mood. This Research Topic aims to illustrate how hormonal mechanisms regulate the nexus between feeding behavior and stress. It focuses on the hormonal regulation of hypothalamic circuits and/or brain dopaminergic systems, as the potential sites controlling the converging pathways between feeding behavior and stress.